DAMPAK STRUKTUR KEPEMILIKAN DAN CORPORATE GOVERNANCE TERHADAP PROFITABILITAS BANK - Cahaya, Yulizar; Hartini, Hartini (Lembaga Penerbitan Unversitas Esa Unggul, 2016)
This study aims to determine the impact of the ownership structure and corporate governance to profitability. The sampling technique used was purposive sampling. The sample used is a company engaged in the conventional banking sector listed in Indonesia Stock Exchange (BEI) and follows corporate governance ratings by The Indonesian Institute for Corporate Governance (IICG) in the period 2010 to 2014. Profitability is measured using return on assets (ROA) and Return on Equity (ROE). The results showed that private ownership has significantly negative effect on ROA and corporate governance have a significant negative impact on ROA and ROE. Variable control of Non-performing loans negatively affect ROE and positive effect on the firm size of ROA and ROE. This research is expected to help managers increase profitability by considering several factors such as private ownership, Corporate Governance Perception Index (CGPI), non-performing loan (NPL) and firm size.Â Key words: CGPI, corporate governance, domestic ownership, foreign ownership, private ownership, profitability, ROA, ROE